ASEAN economic cooperation and integration : progress, challenges and future directions - Chia, Siow Yue; Plummer, Michael G., 1959- (Cambridge, United Kingdom : Cambridge University Press, 2015)
'ASEAN economic cooperation and integration have come a long way since the organisation's early days, when cooperation was more political and diplomatic than economic in nature. ASEAN now constitutes the most ambitious organization of regional cooperation in the developing world. This book investigates the economics of various ASEAN and ASEAN-centric economic integration initiatives, focusing in particular on the ASEAN Economic Community (AEC). In addition to assessing the potential effects of the AEC on the economies of the ten ASEAN member-states via changes in trade, foreign direct investment and economic structure, this book underscores the implementation challenges ASEAN faces as it completes the AEC project. It also considers the AEC in the context of the Regional Comprehensive Economic Partnership (RCEP). This comprehensive study is written for academic researchers and students, as well as for policy makers in ASEAN as they chart the future policy path of the region'--
'This innovative book series evaluates the community-building processes of ASEAN to date and offers a conceptual and policy toolkit for broader Asian thinking and planning of different legal and institutional models of economic and political regional integration in the region'--
Includes bibliographical references and index.
Keywords: International economic relations; Southeast Asia -- Economic integration; Southeast Asia -- Foreign economic relations